Step-by-Step Multi-Ship Collision Avoidance Navigation Path Planning Based on Particle Swarm Optimization - Canglong Zhao (Journal of Control Science and Engineering)
In order to solve the problem that it is difficult to combine path planning with navigation rules in the process of multi-ship collision avoidance in wide waters, a step-by-step multi-ship collision avoidance path planning algorithm is proposed in this paper. Firstly, the obstacle ship is regarded as a static obstacle, and the static path planning is carried out by using the particle swarm optimization path planning algorithm in polar coordinate space combined with the field of ship safety to obtain the turning point of ship collision avoidance. Then, the steering angle of the steering point is dynamically corrected by using the navigation rules. The experimental results show that the particle swarm optimization algorithm finds an optimal path in about 35 iterations, and the shortest path is 38.4 n miles. Conclusion. The algorithm can solve the problem of multi-ship collision avoidance path planning and provide a new idea for solving the problem of multi-ship collision avoidance.